Pemikiran Abdurrahman Wahid tentang Pribumisasi Islam - Fitriah, Ainul (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2013)
This article explores the thought of ?indigenization of Islam? of Abdurrahman Wahid?s. Indigenization of Islam is how the normative teachings of Islam as derived from God and it can be accommodated into the culture derived from human without losing its identity, respectively. As to Abdurrahmad Wahid or Gus Dur, Arabism (or process identifies with the Middle Eastern culture) would deprive us of his own cultural roots. More than that, Arabism is not suitable. Indigenization is not an effort to avoid the emergence of resistance of the power of local cultures, but instead that culture is not lost. The core of indigenization of Islam (Islamic natives) is not a necessity to avoid pillarization between religion and culture, because such polarization is not inevitable.